The impact of teaching games for understanding and direct instruction models on volleyball passing skills based on arm strength - Zaniar Dwi Prihatin Ciptadi; Sigit Nugroho; Desi Adriani; Laishram Thambal Singh (Tanjungpura Journal of Coaching Research)
Background and Study Aim. The Teaching Games for Understanding (TGFU) model emphasizes tactical understanding of the game, while Direct Instruction is more oriented towards explicit instruction and repetitive practice. Therefore, this study aims to analyze the effect of TGFU and Direct Instruction learning models on volleyball lower passing skills based on students' arm strength.